How mafia-like bureaucratic cartels or thieves in suits run corruption inside the bureaucracy, or how government officials swindle citizens in Kenya! - Onyango, Gedion (Deviant behavior, 2024)
As typical of many developing contexts, Kenyans know how most civil servants make an honest living out of public monies - in other words, there is generally nothing wrong with making a living, legal or otherwise, from where one works. But this situation can be more complex than that. Bureaucratic corruption is more about bureaucratic structure and culture (how things are done here), as well as the bureaucracy’s sociopolitical environments. Most importantly, variables relating to bureaucracy’s political outliers show that bureaucratic corruption can also be a tool of regime consolidation, a space of elite struggle for rewards and control. The result is that, a mafia-like white-collar corruption syndicate (cartels) and isolated corrupt practices emerge at all levels and sectors to enforce corruption and swindle citizens through unscrupulous bureaucratic processes. These cartels employ an assortment of enforcement tools to achieve their goals, from exercising official investigations to bribery, kickbacks, threats and murder. Using a multi-dimensional administrative rituals approach, this paper is a modest attempt to understand how these factors produce bureaucratic gray areas that rationalize and institutionalizes corruption and cartel activities. While the solution primarily lies with the political leadership, this cannot happen unless a civil society, instead of the opposition parties-led citizen movement, is reinvigorated in Kenya.